PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN GENERASI Z DENGAN MOTIVASI SEBAGAI MEDIASI PADA PT. GADING MURNI - Rahma Syaufil Fitri; Santirianingrum Soebandhi (CV. Denasya Smart Publisher, 2025)
The growing presence of Generation Z in the workforce has prompted companies to understand the factors that can improve employee performance. The characteristics of Generation Z, which emphasize a comfortable work environment, opportunities for career development, and work-life balance, make the management of the work environment, workload, and work motivation essential for achieving optimal employee performance. This study aims to analyze the effects of the work environment and workload on the performance of Generation Z employees, with work motivation serving as a mediating variable at PT Gading Murni. This research employed a quantitative approach using a survey method. The respondents consisted of 48 Generation Z employees working in the Retail Division of PT Gading Murni. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4. The results indicate that the work environment has a positive and significant effect on work motivation, whereas workload has a negative and significant effect on work motivation. Furthermore, work motivation has a positive and significant effect on employee performance and successfully mediates the relationships between the work environment, workload, and employee performance. Therefore, improving the quality of the work environment and managing workload proportionally through strengthening work motivation can serve as an effective strategy to enhance the performance of Generation Z employees at PT Gading Murni.